Hubungan Antara Strategi Organisasi Praktik Total Quality Management Dengan Financial Performance Pada Perusahaan Jasa Di Provinsi Riau - Basri, Yesi Mutia (Jurnal Ekonomi, 2010)
The purpose of this study is to analyze the relationship between TQM, strategy and financialperformance.This study used a sample which consisted of 52 service companies in Riau Province.However, the respondents only 16, which consists of 2 hospitals, 4 hotels, 8 banks and 2telecommunications companies .Analyis of data using multiple linear analysis with path analysis technique with the SPSS software.The results showed that the strategy of differentiation and cost leadership strategies have significanteffect on TQM practices and TQM practices significant influence.Strategy have strong relation on TQM, but the strategy of differentiation and cost leadership strategydoes not have significant impact on financial performance.